Employee engagement and job performance in Lebanon - Ismail, Hussein Nabil (2019)
Purpose The purpose of this paper is to explore the relationship between employee engagement and job performance in the country of Lebanon, and to test whether creativity mediates the relationship between engagement and performance. Design/methodology/approach The research sample consisted of 186 respondents working in Lebanese firms. The questionnaire included established measures relating to employee engagement, job performance and creativity – in addition to various demographic questions. Stepwise multiple regression and bootstrapping methods were employed in the analysis of the data. Findings The findings showed a significant positive effect of employee engagement on job performance. However, mediation analysis using bootstrapping methods has shown that creativity has fully mediated the relationship between engagement and performance. Originality/value The study extends previous research and increases the external validity of the findings by investigating the relationship between engagement and performance in new non-western contexts. Moreover, this is one of the first research studies that explores the role of creativity in the relationship between the two variables; this helps in improving our understanding of the model and aids in enhancing the effect of engagement on performance.